ANALISIS YURIDIS KEPUTUSAN PN JAKPUS NOMOR 155/PDT.P/2023/PN.JKT.PST TENTANG PERNIKAHAN BEDA AGAMA DAMPAKNYA TERHADAP PERKEMBANGAN HUKUM PERDATA ISLAM DI INDONESIA - Krishnani, Ririh (An Nawawi, 2023)
Interfaith marriage is a serious social issue in Indonesia. As a predominantly religious country, marriage in Indonesia is regulated by Law No. 1 of 1974, which does not accept the validity of interfaith marriages. However, with the passing of Law No. 23 of 2006, it is possible. If an interfaith marriage is legally recognized, it must be registered with the court. Court approval is required. The author uses a normative juridical method. examines the legal considerations of the decision of the Central Jakarta District Court Judge number 155/Pdt.P/2023/PN.Jkt.Pst on Interfaith Marriage. According to the author's analysis, it turns out that the judge has neglected the rules of Islamic law that apply in Indonesian Muslim society, namely by issuing a determination as evidence of the recognition of the validity of interfaith marriages. However, philosophically, the judge did not take into consideration the impact that will be experienced due to interfaith marriages such as the weakening of religious observance in the community which will ultimately become an inhibiting factor in the development or enforcement of Islamic Civil Law in Indonesian Muslim society.